Factors that influencing spending behavior among Sultan Zainal Abidin University students / Iffah Bazilah Zaki - Zaki, Iffah Bazilah (Bachelor of Business Administration (Hons) Marketing, 2015)
The purpose of this paper is to first provide an overview of the students’s spending behavior through three factors which are financial literacy, socialization agents and the brand image. Based on the survey administerd to 100 students in Sultan Zainal Abidin University, a factor analysis is to measure the relationship and the most influential factor that will affect the spending behavior. The result indicate that the financial literacy give the most influence towards the spending behavior. The result also showed that financial literacy and the socialization agents is significant to the spending behavior while the brand image is not significant to it. These result are important to the practiotioners as it shows that this study can be apply to the university to enhance their students’s financial mangement through many ways such as through workshop and classes